PENGARUH PERENCANAAN SUMBER DAYA MANUSIA TERHADAP KINERJA GURU DI SMK DARUSSALAM BLOKAGUNG TEGALSARI BANYUWANGI TAHUN PEMBELAJARAN 2019/2020 - Nawal Ika Susanti; Faizatut Daroeini (Institut Agama Islam Darussalam Blokagung, 2021)
This research is directed at 2 main points, namely (1) Is there any influence of human resource planning on teacher performance in SMK Darussalam Blokagung Banyuwangi 2019/20220 academic year, (2) How big is the effect of human resource planning on teacher performance in SMK Darussalam Blokagung Banyuwangi in the academic year 2019/20220. This research uses quantitative descriptive method with product moment technique in the data validity test and to find the reliability of the data using the alpha formula, while the hypothesis test uses the F test and T test then uses a regression model. The population of this research is 66 Darussalam Blikagung Banyuwangi Vocational School teachers. To measure variables, researchers use questionnaires for human This research is directed at 2 main points, namely (1) Is there any influence of human resource planning on teacher performance in SMK Darussalam Blokagung Banyuwangi 2019/20220 academic year, (2) How big is the effect of human resource planning on teacher performance in SMK Darussalam Blokagung Banyuwangi in the academic year 2019/20220. This research uses quantitative descriptive method with product moment technique in the data validity test and to find the reliability of the data using the alpha formula, while the hypothesis test uses the F test and T test then uses a regression model. The population of this research is 66 Darussalam Blikagung Banyuwangi Vocational School teachers. To measure variables, researchers use questionnaires for human This research is directed at 2 main points, namely (1) Is there any influence of human resource planning on teacher performance in SMK Darussalam Blokagung Banyuwangi 2019/20220 academic year, (2) How big is the effect of human resource planning on teacher performance in SMK Darussalam Blokagung Banyuwangi in the academic year 2019/20220. This research uses quantitative descriptive method with product moment technique in the data validity test and to find the reliability of the data using the alpha formula, while the hypothesis test uses the F test and T test then uses a regression model. The population of this research is 66 Darussalam Blikagung Banyuwangi Vocational School teachers. To measure variables, researchers use questionnaires for human resource planning and teacher performance. After analyzing the data collected, it was found that (1) There was an effect of human resource planning on teacher performance in SMK Darussalam Blokagung Banyuwangi. (2) the effect of the implementation of human resource planning on the performance of teachers in SMK Darussalam Blokagung Banyuwangi by 58%.